Comparison of Binocular Vision Parameters in Patients With Irregular Corneas Corrected With Spectacles Versus Rigid Contact Lenses (RGP, Rose K, & Scleral Lenses) - Sah, Manish; Chaudhry, Monica; Akhtar, Zeeshan; Sah, Ruchika (Canadian Journal of Optometry, 2025)
To compare Binocular vision (BV) parameters between spectacle and rigid lenses among patients with irregular cornea Design: Comparative prospective study Method: All the binocular vision parameters were evaluated on two different occasions in 30 irregular corneas (22 Keratoconus, 3 pellucid marginal degeneration, 2 post-LASIK ectasia and 3 Post graft) patients who wore contact lenses and single vision spectacle had average age of 26±8.0 years. The binocular vision parameters measured in the study were; near the point of accommodation (NPA), accommodative facility, near negative and positive fusional vergence, distance negative fusional vergence (NFV) and positive fusional vergence (PFV), vergence facility, near the point of convergence (NPC), negative relative accommodation (NRA), and positive relative accommodation (PRA), AC: A ratio, and stereo acuity. Result: A total 60 subjects were participated in the study in which 30 was aged match control group & 30 patients with irregular cornea. When a patient with an irregular cornea switched from single vision glasses to rigid contact lenses, their monocular and binocular logMAR distant and near visual acuity (VA), as well as stereoacuity, improved dramatically (P <.05).The stereoacuity with spectacle was 400±60 sec of arc and with rigid contact lens 140±30 sec of arc which were statistically significant (p<0.05). Near horizontal phoria was less with rigid contact lens: -7.50±2.71 as compared to spectacle: -9.67±3.17, but this difference was not statistically significant (p=0.06). . The clinical findings of patient with rigid contact lens were Distance phoria: -4.83±3.35; near phoria: -7.50±2.71 (Negative values in the Phoria indicate exodeviations) and; PRA: 7.22±0.50; stereoacuity: 140.0±30 which were statistically significant compared to aged match control group. (p<0.05). Conclusion: Binocular & monocular logMAR visual acuity, near phoria and stereopsis improve from single vision spectacles to rigid contact lenses in patient with irregular cornea and also all binocular vision parameters with rigid contact lenses among irregular cornea remained poorer than aged matched control subjects.